PATH-34. CLINICOPATHOLOGIC, MOLECULAR AND IMMUNOLOGICAL CHARACTERIZATION OF DIFFUSE MIDLINE GLIOMAS: IS THERE A PROGNOSTIC SIGNIFICANCE?. (11th November 2019) - Manjunath, Niveditha; Jha, Prerna; Raheja, Amol; Suri, Vaishali; Suri, Ashish; Garg, Ajay; Kaur, Kavneet; Sarkar, Chitra
Abstract: H3K27M Diffuse Midline Gliomas (DMGs) are amongst the most fatal cancers, considered WHO grade IV irrespective of the histological features. Treatment modalities have been ineffective in prolonging survival. The aim was to determine the clinico-pathologic, molecular and immunological characteristics of DMGs in children and adults. Genetic (H3K27M, ATRX, IDH1, p53) and immune (CD3, CD8 and PD-L1) profile of 126 DMGs identified over 10 years was studied with immunohistochemistry (IHC). Sanger sequencing performed for IDH1 and H3K27M mutation. Clinico-radiologic characteristics were reviewed and survival analysis performed. Of the 126 DMGs, 49.2% H3K27M mutant and 50.8% wildtype cases (mean age 21.27 years vs. 36.23 years). 75.68% of pediatric whereas 38.20% of adults were H3K27M mutant. Brainstem (46%) was commonest site in H3K27M mutant pediatric cases while majority of adults (62%) were thalamic. H3K27M was mutually exclusive with IDH mutation in 92.5% cases, whereas p53, ATRX mutation was 56.4% and 30.6% respectively. IHC showed 95% concordance with Sanger sequencing for H3K27M mutation. PD-L1 expression was greater in elderly (>50 years), than young adults and pediatric cases (p=0.002). CD8 expression was greater in adult then pediatric cases (p=0.0001). Overall survival (OS) was not statistically significant in mutant versus wildtype cases in children (p=0.45) as well as adults (p=0.65). Tumor location showed no correlation with OS. Tumor resection independently or on correlation with H3K27M did not influence OS (p=0.505 and p=0.470). Adjuvant therapy impacted survival significantly in adults (p=0.0009) than in pediatric patients (p=0.0669) The study highlights the differences in frequency and location of pediatric and adult H3K27M mutant DMGs. Dismal prognosis in both age groups of H3K27M mutant and wild type DMGs. IHC for H3K27M mutation is an excellent substitute to Sanger sequencing. Our analysis emphasises the role of molecular characterisation for the development of effective therapeutic strategies, for different DMG subgroups.